Effects of POGIL and Verification Approaches on Students’ Cognitive Achievement in Reaction Rate: The Moderating Role of Scientific Reasoning - Erga Kurniawati; Thayban Thayban; Haris Munandar (Universitas Negeri Gorontalo, 2026)
This study examined the effectiveness of the Process Oriented Guided Inquiry Learning (POGIL) approach in improving students’ conceptual understanding of reaction-rate concepts and investigated whether scientific reasoning skills moderate the effect of instructional model in a 2×2 factorial design. Forty-four tenth-grade science students from two intact classes were matched and categorized into high and low scientific reasoning groups. Conceptual understanding was measured using a two-tier diagnostic test, and assumptions for Two-Way ANOVA were verified before analysis. Results indicated a significant main effect of instructional model, with POGIL achieving higher scores than verification-based instruction (F = 20.385, p < 0.001, η² = 0.29). Scientific reasoning also significantly influenced outcomes (F = 7.328, p = 0.010, η² = 0.10). The interaction between instructional model and reasoning was not statistically significant (F = 2.559, p = 0.118), indicating that the interaction effect was not statistically significant in this sample. POGIL is theoretically expected to support integration of macroscopic, submicroscopic, and symbolic representations through guided inquiry and collaborative scaffolding. Limitations include the small sample size and quasi-experimental design. These findings highlight the potential of guided inquiry-oriented instruction to enhance conceptual understanding while emphasizing the role of reasoning skills, with cautious interpretation of non-significant interactions.